Formulation and implementation of nonlinear elasticity in advanced constitutive models in geomechanics - Tereza Žalská; Michal Šejnoha; Tomáš Janda; Alena Zemanová (Acta Polytechnica CTU Proceedings)
Several formulations of a nonlinear elastic behavior within the yield surface of the selected advanced constitutive models are described and compared. Since concentrating on geotechnical applications the accompanied numerical simulations are limited to basic laboratory tests such as isotropic compression, oedometer, and drained triaxial compression. The results show a significant influence of the size of the initial load step on final predictions particularly when starting from a very low initial stiffness associated with the assumed zero initial stress. Differences in the predicted response arising from different formulations are also discussed. These might be quite significant and the design engineer should be aware of that when choosing a particular computational software.